Role of Starch Pre-treatment Temperature on types of Cyclodextrins produced from Raw Tapioca Starch - A.M, Mimi Sakinah; Hassan, Osman; A.F, Ismail; A.W, Zularisam; Illias, Rosli Md. (Malaysian Journal of Science, 2008)
The effect of starch pre-treatment temperature and exposure duration of raw tapioca starch on cyclodextrins production using thermostable cyclodextrin glycosyltransferase was investigated in this study. Maximum concentration of cyclodextrins was produced after an hour of exposure duration on raw tapioca starch at 80Ã‚Â°C of the starch pretreatment temperature. Employment of this critical condition as the starch pretreatment procedure promotes high cyclodextrins production as well as better preservation on the starch granule structure. As a matter of fact, the starch critical pretreatment temperature also increased 93% and 94% of swelling power and leached amylose, respectively. All types of cyclodextrin produced revealed significant linear relationship with starch pretreatment temperature.